Development of a method to generate transgenic eggplant (Solanum melongena L.) - Chaithrika, P.A.D.R. (My University, 2010)
Morphogenesisof different explant types of 6-7 weeks old Solanum melongena L. variety " . Padagoda was evaluated in response to different combinations of lAA and BAP in basal MS medium. Leaves and stem pieces (hypocotyls) were found to be more responsive to hormone combinationof 2 mg/L lAA with 1mg/LBAP containedMS mediumfor callusinduction. Calli derivedfrom stem pieces regenerated shoots in the same regeneration medium while no shootregenerationwas achieved calli derived from leaf explants cultured in all four types of hormonecombinations,but root regenerationwas observed only calli derived from leaf explants culturedonregenerationmedium containing 1mg/LBAP only. Best shoot regeneration was obtained in media contained IAA in the presence of BAP with the combination of 2 mg/L lAA with 1 mgIL BAP and 1 gmIL lAA with 1mg/L BAP. Direct shoot regeneration was achieved in media containing high concentration of lAA where MS medium consists of 1mgIL IAA only and MS medium consists of 2 mg/L lAA with 1 mg/L BAP. An independent method of producing transgenic local eggplant (Solanum melongena L) variety Padagoda was carried out by Agrobacterium mediated transformation.6- 7 weeks old leaf and stem pieces were co-cultivated with Agrobacterium tumefaciens strain GV 1301 harboring the binary vector pCAMBIA 1305.1 carrying a modified Bt gene construct cry 1C encoding a lepidopteroninsect-specific Cry 1C toxin under the control of ST-LS1 promoter and NOS terminator.This vector consists of reporter gene ~~glucuronidase(GUSPlus)and the marker gene neomycin phosphotransferase (NPTII).Co-cultivated explants were introduced into callus inductionmedium containing 2mg/1 lAA with 1 mg/L BAP and-250 mg/L cefotaxime. Callus induced explants (stem pieces) were transferred into selection medium containing 2 mg/L lAA with 1 mgIL BAP supplemented with 50 mgIL kanamycin. 33 kanamycin resistance explants (stem pieces) out of 79 were obtained with 19 calli including 4 green calli.